Effects of Early Feed Restriction on Some Performance and Reproductive Parameters in Japanese Quail (Coturnix coturnix japonica) - Fidan , Evrim Dereli; Kaya, Mehmet (International Journal of Poultry Science, 2014)
This study was carried out to investigate the effects of feed restriction on some performance and reproductive parameters in Japanese quails. Two weeks old birds were randomly allocated to three feed restriction groups with three replicates 7 males, 7 females. Body weight, live weight gain, feed conversion ratio were measured during growth period (between 2 to 5 week of age). In egg production period (from 6 to 15 week), body weight and age at first egg, egg production, fertility, hatchability, embryonic mortality, liveability, vitality and hatching chick weight were evaluated from replicates of one female and one male per treatment. In 3rd and 4th weeks of age, body weight was found higher ad libitum group than 15 and 30% restricted feed groups. No treatment differences were observed among body weight within sex groups from 2 to 5 week. In 5th week, average live weight gain of group ad libitum, 15 and 30% feed restriction, 5.18, 6.97 and 8.37 g, respectively. In 12 week of age, hatching chick weight was heavier for 30% feed restriction group than ad libitum group. body weight and age at first egg, egg production, fertility, hatchability, embryonic mortality, liveability and vitality were unaffected by feed restriction. These data indicated that by 30% feed restriction can be practiced for 2 weeks (at 3 and 4 week) during growth period of quail. As a result, 15 and 30% restriction of ad libitum feed intake from 2 to 4 week of age without detrimentally affecting reproductive and hatchability parameters between 6 to 15 week of age.